Pengaruh Karakteristik Individu, Kerja Sama Tim, dan Keterampilan Kerja Terhadap Kinerja Karyawan: Studi Pada Puskesmas Walikukun - Annisa Nur Aqtyas Mahanani; Henri Dwi Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Employee performance plays a crucial role in supporting the effectiveness of public services, particularly in the healthcare sector. This study aims to examine the influence of individual characteristics, team collaboration, and work skills on employee performance at Walikukun Public Health Center (Puskesmas Walikukun). The research employed a quantitative approach using a survey method involving 104 respondents selected through a saturated sampling technique. The research instrument was developed based on theoretical indicators and has been tested for validity and reliability. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the assistance of SmartPLS 3.0 software. The results show that all three independent variables have a positive and significant effect on employee performance. Individual characteristics have a path coefficient of 0.219 (p-value = 0.004), team collaboration 0.376 (p-value = 0.000), and work skills 0.352 (p-value = 0.000). Among these, team collaboration exerts the most dominant influence. These findings underscore the importance of fostering a collaborative work culture and enhancing individual capacity as strategies to optimize employee performance. The practical implications of this study can serve as a reference for health center management in designing competency-based training programs and strengthening teamwork within the workplace.